Recent advances in targeting protein kinases and pseudokinases in cancer biology - Riegel, Kristina; Vijayarangakannan, Parthiban; Kechagioglou, Petros; Bogucka, Katarzyna; Rajalingam, Krishnaraj (Frontiers in Cell and Developmental Biology, 2022)
Kinases still remain the most favorable members of the druggable genome, and there are an increasing number of kinase inhibitors approved by the FDA to treat a variety of cancers. Here, we summarize recent developments in targeting kinases and pseudokinases with some examples. Targeting the cell cycle machinery garnered significant clinical success, however, a large section of the kinome remains understudied. We also review recent developments in the understanding of pseudokinases and discuss approaches how to effectively target them in cancers.